Apparatus and method for automated event notification read receipt to support non-repudiated auditing or other functions in industrial process control and automation system - Duca, Andrew; Burd, Matthew G; Vardy, Tyron (2019)
A method includes transmitting a notification to a first end-user device, where the notification is associated with an event in an industrial process control and automation system. The method also includes receiving a first read receipt identifying when a user of the first end-user device opened the notification or viewed or read details about the notification at the first end-user device. In addition, the method includes storing the first read receipt or information related to the first read receipt in association with the notification and/or the event. The method could also include transmitting the notification to a second end-user device and transmitting a first indication to the second end-user device, where the first indication indicates that the user of the first end-user device opened the notification or viewed or read the details about the notification.